Septic Shock In A Patient With Diabetic Ulcer Complicated By Acute Kidney Failure - Ade Laksono; Agrietia Agrietia (Sean Institute, 2023)
Sepsis is the main cause of death in critically ill patients treated in intensive care units and inpatient rooms. Sepsis is defined as a life-threatening organ dysfunction caused by an uncontrolled host response due to infection. The principles of sepsis therapy consist of fluid resuscitation and hemodynamic support, antibiotics and source control, and a series of adjunctive measures. Inadequate initial treatment of sepsis and septic shock will increase the mortality rate.